Development of Mini Trampoline Equipment Prototype in DKI Jakarta Trampoline Gymnastics - Chandra, Chandra; Nurdin, Fatah; Yuliasih, Yuliasih; Tangkudung, Albert Wolter Aridan (Jurnal Pendidikan Jasmani (JPJ), 2024)
The purpose of this study is to develop a model of mini trampoline equipment for DKI Jakarta trampoline gymnastics athletes, the main purpose is to improve movement skills in gymnastics athletes. Trampoline equipment can be used in training for beginner, junior and senior trampoline gymnastics athletes which can also be used for competitions for trampoline athletes. This research was carried out in several stages, namely the stage of obtaining initial data by making a prototype of a trampoline device, the trial stage which is all qualitative data. The main procedure during this research and development consists of five steps, namely (1) Conducting product analysis to be developed, (2) Developing initial products, (3) Expert Validation, (4) Field Trials, and (5) Product Revision, The results of this study can be concluded that movement skills on mini trampoline tools for trampoline sports can be used to (1) Improve movement skills in mini trampoline equipment of senior and junior athletes, (2) As a training facility for athletes and (3) as a means of entry-level competition